Real Exchange Rates, Income per Capita, and Sectoral Input Shares - Cravino, Javier; Haltenhof, Sam (The Review of Economics and Statistics, 2020)
Aggregate price levels are positively related to GDP per capita across countries. We propose a mechanism that rationalizes this observation through sectoral differences in intermediate input shares. As productivity and income grow, so do wages relative to intermediate input prices, which increases the relative price of nontradables if tradable sectors use intermediate inputs more intensively. We show that sectoral differences in input intensities can account for about half of the observed elasticity of the aggregate price level with respect to GDP per capita. The mechanism has stark implications for industry-level real exchange rates that are strongly supported by the data.